2022
DOI: 10.3389/fnhum.2022.955005
|View full text |Cite
|
Sign up to set email alerts
|

Potential epigenetic mechanisms in psychotherapy: a pilot study on DNA methylation and mentalization change in borderline personality disorder

Abstract: Genetic and early environmental factors are interwoven in the etiology of Borderline Personality Disorder (BPD). Epigenetic mechanisms offer the molecular machinery to adapt to environmental conditions. There are gaps in the knowledge about how epigenetic mechanisms are involved in the effects of early affective environment, development of BPD, and psychotherapy response. We reviewed the available evidence of the effects of psychotherapy on changes in DNA methylation and conducted a pilot study in a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 99 publications
0
1
0
Order By: Relevance
“…A favourable effect of psychotherapies on epigenetic mechanisms associated with the stress response has been cautiously suggested [80]. Also with reservations, results have been reported that point to possible epigenetic biomarkers predictive of the specific effect of behavioural-dialectical psychotherapy in patients with borderline or emotionally unstable personality disorder (ICD-10) [81].…”
Section: Current Psychological Interventionsmentioning
confidence: 99%
“…A favourable effect of psychotherapies on epigenetic mechanisms associated with the stress response has been cautiously suggested [80]. Also with reservations, results have been reported that point to possible epigenetic biomarkers predictive of the specific effect of behavioural-dialectical psychotherapy in patients with borderline or emotionally unstable personality disorder (ICD-10) [81].…”
Section: Current Psychological Interventionsmentioning
confidence: 99%
“…Second, showing the professional community and health authorities the importance of not leaving psychodynamic therapy out of Mental Health policies (de la Parra, Florenzano, & Jiménez, 2005; Jiménez, 1994). In recent years, however, we decided not to invest any more time in convincing colleagues but to build and propose empirical research models of clinical psychoanalytic hypotheses (Jiménez, Botto, Herrera et al., 2018; Jiménez & Altimir, 2019; Altimir & Jiménez, 2020, 2021; Quevedo et al., 2022) or dynamic psychotherapy models that work at the primary level of health care (de la Parra, Zúñiga, Dagnino, & Gómez‐Barris, 2021).…”
Section: Beyond the Controversy: The Way Out Of The Stalematementioning
confidence: 99%
“…Here, methyl group tags annex to DNA regions, governing gene activation or suppression. Research has demonstrated that epigenetic changes like DNA methylation may influence the interplay between genes and the environment and affect neurodevelopment in the context of BPD [ 18 ].…”
Section: Reviewmentioning
confidence: 99%
“…A pilot study in 2022 conducted by Quevedo in 11 females with early trauma found stress reduction seen in peripheral FKBP5 response protein methylation in response to BPD psychotherapy. The results implied that psychotherapy affects epigenetics involved in BPD's development and psychotherapeutic response [ 44 ]. A study in 2017 led by Knoblich et al, involving 88 participants (comprising 37 females and seven males diagnosed with BPD, matched with 44 healthy controls), found elevated methylation levels in APBA3 and MCF2 among those responding to a 12-week DBT program, emphasizing the predictive power of genetic indicators in BPD treatment [ 45 ].…”
Section: Reviewmentioning
confidence: 99%